Renovation of Old Building Facades. Analysis of Post-Soviet Countries’ Experience and a Proposed Methodology for Community Engagement - Trigub, Ruslana; Domin, Artem (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article examines the problem of the disorderly condition of residential building facades in Ukrainian cities, which has emerged as a result of Soviet urban space management policies, public indifference to the shared urban environment, and the lack of effective urban policy after independence. The differences between approaches to the renovation of mass-panel housing and historic buildings are analyzed: in the former case, priority is given to residents’ comfort and needs, while in the latter—to the preservation of cultural heritage and the authenticity of urban space. Examples of modernization programs from Poland and Estonia are presented, demonstrating the effectiveness of renovation policies under two different approaches. A methodology for community engagement during the planning and implementation of renovation projects is proposed, with an emphasis on building residents’ trust and ensuring proper communication, which enables more effective adjustments to proposed plans and helps prevent potential problems. Systematic renovation contributes to improving quality of life, fostering economic development of districts, and shaping an attractive urban environment.